2022
DOI: 10.1016/j.esmoop.2021.100308
|View full text |Cite
|
Sign up to set email alerts
|

Integrative molecular analysis of combined small-cell lung carcinomas identifies major subtypes with different therapeutic opportunities

Abstract: Background: Combined small-cell lung cancer (C-SCLC) is composed of SCLC admixed with a non-small-cell cancer component. They currently receive the same treatment as SCLC. The recent evidence that SCLC may belong to either of two lineages, neuroendocrine (NE) or non-NE, with different vulnerability to specific cell death pathways such as ferroptosis, opens new therapeutic opportunities also for C-SCLC. Materials and methods: Thirteen C-SCLCs, including five with adenocarcinoma (CoADC), five with large-cell neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Currently, the three-port approach is the conventional choice for thoracoscopic radical pneumonectomy [ 9 ], but the continuous optimization of medical technology has also confirmed the effectiveness of the single-port approach. Prior literature has partially compared the therapeutic efficacy of the three-port approach with the single-port approach [ 10 ], albeit evidence was untenable given the small sample size and unidentified mechanism. Accordingly, this study was to investigate the clinical efficacy of conventional three-port thoracoscopic lobectomy versus single-port thoracoscopic lobectomy for the treatment of lung cancer by examining the impact of different approaches on patients' perioperative indices.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the three-port approach is the conventional choice for thoracoscopic radical pneumonectomy [ 9 ], but the continuous optimization of medical technology has also confirmed the effectiveness of the single-port approach. Prior literature has partially compared the therapeutic efficacy of the three-port approach with the single-port approach [ 10 ], albeit evidence was untenable given the small sample size and unidentified mechanism. Accordingly, this study was to investigate the clinical efficacy of conventional three-port thoracoscopic lobectomy versus single-port thoracoscopic lobectomy for the treatment of lung cancer by examining the impact of different approaches on patients' perioperative indices.…”
Section: Introductionmentioning
confidence: 99%
“…It was thought that surgery therapy is mostly suitable for the patients with early-stage C-SCLC ( 13 ). Our study showed the all-different-staged patients without surgery were significantly associated with a bigger HR and were referred to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by a Chinese group suggested that combined SCLC components are derived from the same pluripotent clonal stem cells and share initial driver mutations with subsequent genomic alterations [17]. However, pulmonary combined SCLC and combined large-cell neuroendocrine carcinoma (combined LCNEC) were noted to possess different interacting driver genes, as exemplified by the lower incidence of EGFR mutations in combined SCLC than in combined LCNEC (5% vs. 25.7%, p = 0.004) [18].…”
Section: Genomic and Treatment Landscape Of Combined Small-cell Lung ...mentioning
confidence: 99%
“…TP53 and RB1 were the most altered genes in 12 patients (83.3% and 66.7%, respectively). Another case series of 13 combined SCLC patients showed KRAS G12C (2/13), PI3KCA (2/13), and EGFR (1/13) alterations, which are potentially targetable [17]. Other frequently noted genes in combined SCLC are PTEN, TERT, ARID1B, SDHA, NF1, NOTCH2, NOTCH1, ALK, FGFR4, FGFR1, SOX2, NOTCH3, KMT2D, FAT1, and FAM135B [18,19].…”
Section: Genomic and Treatment Landscape Of Combined Small-cell Lung ...mentioning
confidence: 99%